IMPLEMENTASI PERATURAN TENTANG TATA BANGUNAN DI JALAN TEUKU UMAR DENPASAR - Tony Marthana Wijaya, Putu (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 3 No 1 (2016): April 2016DO - 10.24843/JRS.2016.v03.i01.p07, 2016)
Abstract Kota Denpasar Local Government has instigated a set of guidelines to regulate urban development. These focus on both space and building design. The objective is to create harmony within its projected cultural environment. The implementation of these regulations however raise serious concerns since current inconsistencies appear to suggest that few prevailing regulations are currently in force. This study has three goals: first to investigate developments that violate existing spatial planning and building design guidelines; second, to research factors that support underlines such violations; and third to suggest such actions as will promote compliance and enforcement of all regulatory practices, both current and future in order to promote the government’s own intention of creating a ‘cultural city in Denpasar . This study uses a qualitative research approach that focuses on hegemonic control and the commodification of space. These factors come into play when there is a clear difference between the issuance of a building permit and the final construct. Inconsistencies frequently appear in regard to the commodification of public space and building facades in general. This is encouraged by two dominant factors. First there is the lack of appropriate control and monitoring by relevant government agencies, and secondly, the absence of sanctions when violation takes place. Here the government can be seen to defeat its own objective of Denpasar as ‘a cultural city.’ This study suggests community participation and sanction constitute a necessary force in removing this contradiction currently prevailing in government policy. Keywords: regulation, violations, spatial plan, building design guidelines. Abstrak Pemerintah Kota Denpasar memandang sebagai keharusan untuk mengatur dan mengendalikan lajunya pembangunan yang berfokus pada keruangan dan desain bangunan. Tujuannya adalah menjaga keharmonisan serta keserasian wajah kota yang berwawasan budaya. Implementasi dari peraturan-peraturan tersebut menjadi pertanyaan dikarenakan adanya perbedaan antara harapan dengan kenyataan terhadap tata bangunan. Analisis ini akan diarahkan pada uraian deskriptif mengenai realita penyimpangan yang terjadi di lokasi, faktor-faktor yang menyebabkan penyimpangan-penyimpangan itu tetap terjadi. Permasalahan tersebut dianalisis dengan teori hegemoni dan komodifikasi. Hasil penelitian menunjukkan bahwa terdapat penyimpangan antara dokumen IMB yang dimiliki dengan realita di lapangan. Adanya komodifikasi terhadap ruang terbuka/ sempadan dan tampak bangunan. Peraturan yang ada tidak dapat terimplementasi dengan baik di lapangan. Kurang konsistennya pengawasan dan penertiban yang dilakukan oleh instansi terkait dan rendahnya sanksi sebagai penyebabnya. Kesimpulan yang diperoleh perlu adanya peran serta masyarakat bersama pemerintah untuk konsisten terhadap penegakkan peraturan tata bangunan agar terciptanya wajah kota yang berwawasan budaya. Kata kunci: peraturan, penyimpangan, rencana tata ruang, tata bangunan.
Keywords: peraturan, penyimpangan, rencana tata ruang, tata bangunan.